Controlling the Message and the Medium?: The impact of sports organisations' digital and social channels on media access. Issue 5 (28th May 2017) - Sherwood, Merryn; Nicholson, Matthew; Marjoribanks, Timothy
Abstract : Sports organisations' recently acquired ability to deliver their own news—through social and digital platforms—represents a potential paradigm shift in the once symbiotic relationship between sports organisations and the media that cover them. While sports organisations once needed the media to deliver their messages, they now have their own media. This study examined the impact of sports digital and social platforms, such as websites, Twitter and Facebook, on sports journalism through 37 interviews with public relations staff in Australian sports organisations and one targeted case study in a professional Australian Rules Football club competing in the Australian Football League (AFL) in Australia. It found that while public relations staff in Australian sports organisations still value traditional media coverage, they also signalled that their own platforms were increasing in value as distribution channels. The case study of the professional AFL club found that the club selectively chose to distribute some stories on their own platforms instead of through traditional media. These stories were not simply delivered on the club's own platforms, but the public relations staff actively framed the narrative of these stories for strategic benefit. These results have significant implications for sports journalism, as it suggests the rapid development of sports organisations' social and digital media platforms has the potential to irrevocably alter the once symbiotic relationship between sport and media.